Visual Branding Kemasan Produk Olahan Belimbing Khas Depok: Studi Kasus Merek Rasa Dewa - Listya, Ariefika (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2017)
This research focuses on visual branding study of superior featured product of local area which produce by SMEs in Depok. Depok has a featured product which is starfruit called â€œbelimbing Dewaâ€. Rasa Dewa is one of many brands of Depokâ€™s proccessed product of starfruit which have lot of variants among others brand. This qualitative research uses aesthetic approach (form, function, meaning) and marketing science approach. Data are collected by observation and literature study. it was done by observed the visual branding elements on the packaging. The Packaging of Rasa Dewa were analyzed according to the regional branding concept whereby the use of geographic indicators on brand identity may involve associations of unique characteristic qualities with specific locations or quality images based on the history, tradition and folklore of an area. The purposes of this study are to determine the form, function and meaning of the elements of Visual Branding of Rasa Dewa that exist on the packaging of starfruit processed products which produces by SMEs Depok associated to brand identity and brand image as a featured product of the local area. Result of this research indicate that Packaging of Rasa Dewa not yet represent Depok featured product.